Impact of Physical Activity Level on Psychological Health of Postgraduate Students of Savitribai Phule Pune University - Jalmi Chinmay; Suman Pandey Mahadevan (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
The purpose of the study was to study the Impact of Physical Activity Level on the Psychological Health of the students of Savitribai Phule Pune University (SPPU). which 164 students from SPPU were selected using a Purposive sampling technique. The Descriptive Comparative method was administered to determine if there is a significant difference in Psychological Health among students of SPPU with respect to their Physical Activity Level. The Mean and S.D. of Psychological Health of Highly Active Male was 35.48(±13.896) and for Highly Active Female was 31.2 (±13.79), the Mean and S.D. of Psychological Health of Active Male was 39.75 (±18.714) and for Active Female was 31(±29.051) respectively, the Mean and S.D. of Psychological Health of Moderately Active Male was 43.77(±18.77) and for Moderately Active Female was 46.71 (±20.65) respectively, the Mean and S.D. of Psychological Health of Low Active Male was 37.77(±23.67) and for Low Active Female was 49(±17.62) respectively. The Mean and S.D. of Psychological Health of Sedentary Male were 35.44(±15.75) and for Sedentary Female were 50.81(±17.88), respectively. Statistical tools such as Descriptive statistics, one-way ANOVA and Post hoc test were used to analyse the data. The results of ANOVA showed that the F-value for females was 4.015 (p=0.005), indicating a significant difference in psychological health among females based on their physical activity level. Further, the F value in males was 0.529 (p=0.715), which shows that there was no significant difference in the psychological health of males based on physical activity level. Therefore, it can be concluded that there is a significant difference in psychological health among females, depending on their Physical activity level.